1997
DOI: 10.1038/sj.onc.1200873
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the p185neu transmembrane domain is necessary but not sufficient for transformation

Abstract: The neu proto-oncogene encodes a receptor tyrosine kinase (RTK). The oncogenic allele neu* (p185*) bears a glutamic acid for valine substitution at position 664 within the predicted transmembrane domain. We have used this mutant to explore the role of the transmembrane domain in signal transduction by RTKs. Analysis of a panel of neu* proteins with second-site mutations in the transmembrane domain revealed a strong correlation of dimerization with transformation. Both dimerization and transformation are depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 24 publications
4
65
1
Order By: Relevance
“…C-terminus is the most variable region among the receptors provided for the use of juxtamembrane mutations as a readily controlled arti®cial experimental system for the induction of dimerization (Sorokin et al, 1994). Surprisingly, it was found that, depending on the location of the cysteine mutations introduced, stable dimers could be induced without concomitant transforation (Sorokin et al, 1994), a result supported by a later study utilizing a transplanted dimerization-inducing transmembrane domain (Burke et al, 1997). Upon further investigation, receptors with mutations that led to transforming receptor complexes all formed dimers involving the same predicted helical interface, strongly suggesting a steric constraint for p185neu activation (Burke and Stern, 1998).…”
Section: Insights From the Transmembrane Domainmentioning
confidence: 49%
See 1 more Smart Citation
“…C-terminus is the most variable region among the receptors provided for the use of juxtamembrane mutations as a readily controlled arti®cial experimental system for the induction of dimerization (Sorokin et al, 1994). Surprisingly, it was found that, depending on the location of the cysteine mutations introduced, stable dimers could be induced without concomitant transforation (Sorokin et al, 1994), a result supported by a later study utilizing a transplanted dimerization-inducing transmembrane domain (Burke et al, 1997). Upon further investigation, receptors with mutations that led to transforming receptor complexes all formed dimers involving the same predicted helical interface, strongly suggesting a steric constraint for p185neu activation (Burke and Stern, 1998).…”
Section: Insights From the Transmembrane Domainmentioning
confidence: 49%
“…Bargmann and Weinberg (1988) noted that mutation of either residues 663 or 665, the residues immediately adjacent to the mutation observer in rat neu, to Glu did not lead to transformation. Other groups have pursued this observation, investigating the importance of residues surrounding the point mutation and more closely examining the location constraints for a transforming mutation (Burke et al, 1997;Cao et al, 1992). By generating a battery of both random and rationally designed potential transmembrane sequences, Chen et al (1997) found a critical limitation for spacing between residues with the potential for hydrogen bonding, suggesting a possible rotational constraint.…”
Section: Insights From the Transmembrane Domainmentioning
confidence: 99%
“…Superposing ErbB2 extracellular regions on either domain II or domain IV contact regions of EGFR/ErbB dimers demonstrates that ErbB2 is not capable of simultaneously forming favorable domain II dimer contacts and bringing the juxtamembrane regions of domain IV into close proximity (Fig. 5), which appears to be a feature of ErbB signaling (4,13,24). Unlike Drosophila EGFR, ligand binding is not required for ErbB2 to participate in active signaling complexes owing to the presence of ligand-binding homologs, which allowed ErbB2 to evolve a fixed straight domain II conformation and specialize as a heterodimerization partner.…”
Section: Resultsmentioning
confidence: 99%
“…What are the consequences of these mutations on the function of FLT3 and pathophysiology of AML? Although the mechanism of activation of FLT3 has not been extensively studied, insights into the role of these mutations can be gleaned from analysis of other nonreceptor TK and receptor TK, including the Eph, 104-107 ERBB2, 108,109 insulinlike growth factor 1 receptor (IGF-1R), 110 fibroblast growth factor receptor 1 (FGFR1), 111,112 and epidermal growth factor (EGF) receptors. 113 The RTKs have autoinhibitory domains that maintain the kinase in an inactive conformation.…”
Section: General Mechanisms Of Rtk Activation: Relevance To Flt3 Mutamentioning
confidence: 99%